A high-temperature resistant two-component high-frequency wood splicing adhesive and its preparation method
By preparing high-temperature resistant two-component high-frequency wood panel glue composed of styrene acrylic emulsion, acrylic emulsion, etc., the problems of poor polarity and insufficient water resistance in high-frequency panels are solved, and efficient curing and high bonding strength are achieved, which is suitable for high-frequency hardwood panels.
Patent Information
- Application Number
- CN202210624277.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-06-02
- Publication Date
- 2025-07-25
- Estimated Expiration
- 2042-06-02
AI Technical Summary
The existing cold pressed patchwork glue has poor polarity in high-frequency patchwork, resulting in poor effect of high-frequency patchwork, especially when applied to medium-hard wood. The traditional patchwork glue raw materials contain substances that harm the human body, and the preparation steps are cumbersome and poor water resistance.
High temperature resistant two-component high-frequency wood panel glue consisting of styrene acrylic emulsion, acrylic emulsion, epoxy resin emulsion, polyvinyl alcohol, inorganic particles, additives, defoaming agents, fungicides and alkalis is prepared through specific proportions and processes to improve the polarity, bonding strength and water resistance of the glue.
The prepared patch glue has high polarity and bonding strength, and can cure quickly in high-frequency patch panels, save process time and improve production efficiency. It is suitable for high-frequency hardwood patch panels and is used in winter or cold areas without damaging the tool.
Smart Images

Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the field of adhesives, in particular to the IPC C09J131 field. More specifically, it relates to a high-temperature-resistant two-component high-frequency wood splice adhesive and a preparation method thereof. Background Art
[0002] Ordinary solid wood splice adhesives can be water-resistant and weather-resistant, with high strength, and are suitable for cold splicing at room temperature. The pressing time generally needs to be more than 1 hour. However, when splicing boards at room temperature, the pressing time is too long, the splicing equipment is large in volume, occupies a lot of workshop area, and customers need to improve production efficiency. Moreover, it is required that the splicing equipment occupies a small workshop site, and a new high-frequency splicing process is becoming more and more common. However, the connection of high-frequency splicing relies on the electromagnetic oscillation generated by a high-frequency machine to cause the molecules in the adhesive to collide, thereby generating heat, promoting the rapid curing of the adhesive in a very short time, and thus completing the splicing process, greatly saving the process time and improving the efficiency. However, for electromagnetic high-frequency heating, the adhesive needs to have good polarity. Ordinary cold-pressed splice adhesives have poor polarity, resulting in poor high-frequency splicing effects, especially when applied to the high-frequency splicing of some medium-hard woods, and the conventional cold-pressed splice adhesives on the market have even worse effects.
[0003] In the prior art, the patent application document with the authorization announcement number of CN103409087B discloses a one-component splice adhesive and a preparation method thereof. The preparation raw materials of the splice adhesive are: polyvinyl alcohol, non-ionic emulsifier, anionic emulsifier, vinyl acetate, acrylic acid, pentaerythritol triacrylate, N-methylol acrylamide, dibutyl phthalate, etc. By introducing crosslinking functional monomers such as pentaerythritol triacrylate, N-methylol acrylamide, and acrylic acid, the water resistance of the water-based adhesive is improved, and it does not need to be prepared and used immediately, which is convenient to use. However, dibutyl phthalate in the raw materials is harmful to the human body and is internationally prohibited, and it does not significantly improve the polarity of the splice adhesive.
[0004] The patent application document with the application publication number of CN108018006A discloses a splice adhesive. The preparation raw materials of the splice adhesive are: styrene-acrylic emulsion, heavy calcium, polyvinyl alcohol emulsion, vinyl acetate-acrylic emulsion, ethylene-vinyl acetate copolymer emulsion, water, plasticizer, defoamer. The prepared splice adhesive has good water and heat resistance, but its preparation steps are cumbersome and its water resistance is poor.
[0005] Therefore, it is necessary to develop a product that not only has good water and heat resistance and stability, but also has high polarity and can be applied to high-frequency splicing, especially high-frequency hard-wood splicing. Summary of the Invention
[0006] To solve the above problems, in the first aspect of the present invention, a high-temperature resistant two-component high-frequency wood splice adhesive is provided, which contains the following raw materials by weight: 30-50 parts of styrene-acrylic emulsion, 5-10 parts of acrylic emulsion, 10-25 parts of epoxy resin emulsion, 5-10 parts of polyvinyl alcohol, 20-40 parts of inorganic particles, 10-20 parts of additives, 1-2 parts of plasticizer, 1-2 parts of defoamer, 1-2 parts of bactericide, and 1-10 parts of alkali.
[0007] Preferably, the splice adhesive contains the following raw materials by weight: 35-50 parts of styrene-acrylic emulsion, 5-8 parts of acrylic emulsion, 15-20 parts of epoxy resin emulsion, 5-8 parts of polyvinyl alcohol, 20-35 parts of inorganic particles, 10-15 parts of additives, 1-2 parts of plasticizer, 1-2 parts of defoamer, 1-2 parts of bactericide, and 3-8 parts of alkali.
[0008] Preferably, the preparation method of the styrene-acrylic emulsion is as follows: by weight, 20-40 parts of styrene and 15-35 parts of butyl acrylate are added to a reaction kettle. After heating to 65-85°C, 1-3 parts of anionic emulsifier, 2-6 parts of oxidant, and 2-7 parts of reductant are added. After reacting for 4-6 hours, the temperature is lowered to below 40°C to obtain the product.
[0009] Preferably, the anionic emulsifier is one or more of sodium stearate, sodium dodecylbenzenesulfonate, didodecyl phenyl ether disulfonate, and sulfonated lignin; more preferably, it is sodium dodecylbenzenesulfonate.
[0010] Preferably, the oxidant is one or more of tert-butyl hydroperoxide, hydrogen peroxide, potassium dichromate, potassium perborate, and potassium persulfate; more preferably, it is tert-butyl hydroperoxide.
[0011] Preferably, the reductant is one or more of ferrous sulfate, thiourea dioxide, and sodium bisulfite; more preferably, it is thiourea dioxide.
[0012] Preferably, the solid content of the acrylic emulsion is 40-60%, and the viscosity is 2000-7000 mPa·s; more preferably, the solid content of the acrylic emulsion is 45-50%, and the viscosity is 3000-5000 mPa·s.
[0013] In some preferred embodiments, the acrylic emulsion can be commercially available, such as 1108S produced by supplier BASF Corporation of the United States.
[0014] Preferably, the mass ratio of the acrylic emulsion to the styrene-acrylic emulsion is 1:(6-10); more preferably, it is 1:6.
[0015] Preferably, the epoxy equivalent of the epoxy resin emulsion is 150 - 300 g / mol; more preferably, it is 210 - 230 g / mol.
[0016] In some preferred embodiments, the epoxy resin emulsion can be commercially available, such as WSR 6101 produced by Shandong Pinsheng New Materials Co., Ltd.
[0017] As a raw material for the finger joint glue, although the styrene-acrylic emulsion has low pollution, good high-temperature resistance and water resistance, its bonding strength is low and it is relatively soft itself, making it not suitable for good adhesive curing when applied to high-frequency finger joint glue. The applicant found that when an acrylic emulsion is added to the raw materials and the mass ratio of the acrylic emulsion to the styrene-acrylic emulsion is 1:(6 - 10), the prepared finger joint glue not only has high bonding strength, high water resistance and high-temperature resistance, but also has high polarity. This may be because acrylic contains carboxyl groups and carbon-carbon double bonds and is a hydrophilic monomer, which can react with the styrene-acrylic emulsion, making the copolymer molecular chain carry carboxyl groups. The carboxyl groups have high polarity and can provide appropriate crosslinking sites for the curing reaction, enabling the polymer to form a network structure, thereby improving the polarity and bonding strength of the finger joint glue, being beneficial to improving the adhesion of the finger joint glue on the surface of hardwood boards, making the prepared finger joint glue suitable for high-frequency operation and capable of being applied to high-frequency finger jointing, especially high-frequency hardwood finger jointing. The addition of the epoxy resin emulsion with an epoxy equivalent of 150 - 300 g / mol can synergistically act with the styrene-acrylic emulsion and acrylic emulsion in this application, while increasing the polarity of the high-frequency finger joint glue, enhancing its boiling water resistance performance.
[0018] Preferably, the viscosity of the polyvinyl alcohol is 5 - 30 cps, the relative molecular mass is 100,000 - 150,000, and the average molecular degree of polymerization is 1,000 - 3,000; more preferably, the viscosity of the polyvinyl alcohol is 21 - 26 cps, the relative molecular mass is 118,000 - 124,000, and the average molecular degree of polymerization is 1,700 - 1,800.
[0019] In some preferred embodiments, the polyvinyl alcohol can be commercially available, such as polyvinyl alcohol BP-17 produced by Changchun Chemical Co., Ltd., Taiwan, China.
[0020] Preferably, the weight ratio of the polyvinyl alcohol to the acrylic emulsion is 1:(0.5 - 2); more preferably, it is 1:1.
[0021] The applicant accidentally discovered that adding a certain amount of polyvinyl alcohol can further improve the bonding strength and economic benefits of the high-frequency splicing adhesive. This may be because polyvinyl alcohol is inexpensive, and there are a large number of hydrophilic groups, hydroxyl groups, in its molecules. The more hydrophilic hydroxyl groups there are, the more hydrogen bonds are formed between the hydroxyl groups, and the more difficult it is for water molecules to enter the crystalline part, thus improving the bonding strength of the high-frequency splicing adhesive. However, using too much polyvinyl alcohol will damage the water resistance of the splicing adhesive. The applicant accidentally discovered that when the weight ratio of polyvinyl alcohol to acrylic emulsion is 1:(0.5 - 2), polyvinyl alcohol can act synergistically with the acrylic emulsion to improve the bonding strength of the high-frequency splicing adhesive while improving its water resistance.
[0022] Preferably, the inorganic particles are selected from one or more of silicon oxide, calcium carbonate, titanium oxide, iron oxide, kaolin, aluminum oxide, and zinc oxide; more preferably, they are calcium carbonate and kaolin.
[0023] Preferably, the weight ratio of calcium carbonate to kaolin is (1 - 2):(1 - 2); more preferably, it is 1:1.
[0024] Preferably, the particle size of the inorganic particles is 400 - 2000 mesh.
[0025] Preferably, the particle size of the calcium carbonate is 400 - 1200 mesh; more preferably, it is 800 mesh.
[0026] In some preferred embodiments, the calcium carbonate with a particle size of 800 mesh is commercially available, such as the ultrafine calcium carbonate powder CC902 produced by Guangxi Hezhou Kelong Powder Co., Ltd.
[0027] Preferably, the particle size of the kaolin is 1000 - 2000 mesh; more preferably, it is 1250 mesh.
[0028] In some preferred embodiments, the kaolin with a particle size of 1250 mesh is commercially available, such as the kaolin produced by Runshi Mineral Powder Factory.
[0029] In order to improve the thermal stability of high-frequency splicing adhesive, inorganic particles are selected as raw materials to enhance the thermal stability of high-frequency splicing adhesive. The applicant found that using calcium carbonate with a particle size of 800 mesh as the inorganic particles can improve the thermal stability of high-frequency splicing adhesive. This may be because calcium carbonate has a large specific surface area, the surface active atoms are in a highly activated state, and there is a strong interfacial interaction with the polymer. Therefore, it can accelerate its cross-linking reaction and greatly improve the dimensional stability and heat resistance stability of high-frequency splicing adhesive. However, if the particle size is too small, it will easily cause agglomeration and affect its application in the system. On the other hand, a high calcium powder content will make the adhesive layer of the benzene system hard and easily damage the cutting tool. The applicant unexpectedly found that using a certain amount of kaolin with a particle size of 1250 mesh as the inorganic particles, the kaolin and calcium carbonate act synergistically. While improving the thermal stability of high-frequency splicing adhesive, it can also improve the hardness of the adhesive layer, making the adhesive layer soft, not damaging the cutting tool, and saving the cutting tool cost.
[0030] Preferably, the auxiliary agent is a film-forming auxiliary agent.
[0031] The film-forming auxiliary agent is one or more of ethylene glycol, ethylene glycol diacetate, dipropylene glycol monobutyl ether, dodecyl alcohol ester, hexylene glycol butyl ether acetate, benzyl alcohol, ethylene glycol butyl ether, ethyl 3-ethoxypropionate, 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate; further preferably, it is 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate.
[0032] In some preferred embodiments, the auxiliary agent can be commercially available, such as the film-forming auxiliary agent produced by supplier Guangzhou Hengyu Chemical Co., Ltd.
[0033] Ordinary splicing adhesives are highly affected by temperature and are not easy to form a film at low temperatures, which affects their application in winter or cold regions. The applicant unexpectedly found that adding a certain amount of 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate as a film-forming auxiliary agent can, without affecting the stability of high-frequency splicing adhesive, also reduce its film-forming temperature, enabling the high-frequency splicing adhesive prepared in this application to be used in winter or cold regions.
[0034] Preferably, the defoaming agent contains silicone components; the density of the defoaming agent is 0.5 - 1.5 g / cm 3 , and the viscosity is 100 - 300 mPa·s.
[0035] In some preferred embodiments, the defoaming agent containing silicone with a density of 0.5 - 1.5 g / cm 3 , and a viscosity of 100 - 300 mPa·s can be commercially available, such as the defoaming agent SI 2293 produced by supplier BASF.
[0036] The applicant found that selecting an antifoaming agent containing silicone with a density of 0.5 - 1.5 g / cm 3 and a viscosity of 100 - 300 mPa·s can improve the shear strength of the high-frequency splicing adhesive. This may be because the silicone in the antifoaming agent has good compatibility with the styrene-acrylic emulsion, can interact with it to form hydrogen bonds, and plays a role in stabilizing and eliminating bubbles, making the cured high-frequency splicing adhesive have good uniformity and no bubbles, thereby improving the shear strength of the splicing adhesive. Moreover, it also interacts with the acrylic emulsion to form a dense surface film layer after curing, reducing the chance of external particles entering the interior of the high-frequency splicing adhesive and improving the stability of the high-frequency splicing adhesive.
[0037] The plasticizer is a non-phthalate plasticizer; the specific gravity of the plasticizer is 0.1 - 2 (20 °C), and the volatile loss is less than 15%.
[0038] In some preferred embodiments, the plasticizer with a specific gravity of 0.1 - 2 (20 °C) and a volatile loss of less than 15% is commercially available, such as Eastman 168 produced by the supplier Eastman Chemical Company of the United States.
[0039] Preferably, the main component of the bactericide is one or more of 7-ethylbicyclooxazolidine, 5-chloro-2-methyl-4-isothiazolin-3-one, and 2-methyl-4-isothiazolin-3-one; more preferably, it is 7-ethylbicyclooxazolidine.
[0040] The active ingredient of the bactericide is 90 - 100%, and the surface tension is 30 - 40 dynes / cm.
[0041] In some preferred embodiments, the bactericide with an active ingredient of 90 - 100% and a surface tension of 30 - 40 dynes / cm is commercially available, such as the mildew-proof bactericide BIOBANTM CS-1246 produced by the supplier Dow Chemical Company of the United States.
[0042] The second aspect of the present invention provides a method for preparing the above-mentioned high-temperature resistant two-component high-frequency wood splicing adhesive, comprising the following steps:
[0043] S1. Prepare the styrene-acrylic emulsion;
[0044] S2. Prepare the polyvinyl alcohol solution: Add polyvinyl alcohol and water to the reaction kettle, heat to 80 - 100 °C, stir for 1 - 3 h, and then cool to below 40 °C to obtain it.
[0045] S3. Mix the prepared styrene-acrylic emulsion, acrylic emulsion, epoxy resin emulsion, and polyvinyl alcohol solution, and add them to the reaction kettle and stir for 20 - 40 min;
[0046] S4. Add inorganic particles to the solution in step S3 and stir for 2 - 5 h at a temperature of 20 - 30 °C;
[0047] S5. Add an auxiliary agent, a plasticizer, an antifoaming agent, and a bactericide to the solution in step S4, and add an appropriate amount of deionized water to adjust the viscosity to 5000 - 20000 cps and the solid content to 50 - 60%;
[0048] S6. Add an alkali to the solution in step S5 to adjust the pH value to 5 - 7, and then it is obtained.
[0049] Preferably, the solid content of polyvinyl alcohol in the aqueous polyvinyl alcohol solution in step S2 is 15 - 25%.
[0050] Preferably, the alkali in step S6 is selected from one or more of sodium hydroxide, potassium hydroxide, sodium carbonate, sodium bicarbonate, ammonia water, and calcium hydroxide; more preferably, it is sodium hydroxide.
[0051] Beneficial effects:
[0052] 1. By selecting an acrylic emulsion and a styrene - acrylic emulsion with a mass ratio of 1:(6 - 10), the prepared finger - joint glue not only has high bonding strength, good water resistance, but also good polarity, can be applied to high - frequency finger - jointing, and when combined with an epoxy resin emulsion with an epoxy equivalent of 150 - 300 g / mol, can improve the boiling water resistance performance of the high - frequency finger - joint glue.
[0053] 2. Selecting an antifoaming agent containing silicone with a density of 0.5 - 1.5 g / cm 3 and a viscosity of 100 - 300 mPa·s can improve the shear strength of the high - frequency finger - joint glue.
[0054] 3. Selecting calcium carbonate and kaolin with a weight ratio of (1 - 2):(1 - 2) as inorganic particles can not only improve the thermal stability of the high - frequency finger - joint glue, but also improve the hardness of the glue layer, making the glue layer soft, not damaging the cutting tool, and saving the tool cost.
[0055] 4. Selecting 2,2,4 - trimethyl - 1,3 - pentanediol monoisobutyrate as a film - forming auxiliary agent can, without affecting the stability of the high - frequency finger - joint glue, also reduce its film - forming temperature.
[0056] 5. The high - temperature - resistant two - component high - frequency wood finger - joint glue prepared by the present invention has good polarity, can be applied to a high - frequency machine, can be quickly cured in a very short time, greatly saves the process time, improves the production efficiency, and has high economic benefits.
[0057] 6. The high - frequency finger - joint glue prepared by the present invention not only has good boiling water resistance performance, high stability, low film - forming temperature, high softness, but also has good polarity of the glue, is suitable for high - frequency operation, and can be applied to high - frequency finger - jointing, especially high - frequency hardwood finger - jointing.
[0058] 7. The high-temperature resistant two-component high-frequency wood splicing adhesive prepared by the present invention is not only applicable to solid wood furniture, but also can be applied to doors and windows, wooden floors, musical instruments, etc. Detailed implementation mode
[0059] Example
[0060] Example 1
[0061] Example 1 provides a high-temperature resistant two-component high-frequency wood splicing adhesive. Calculated by weight, its preparation raw materials include: 48 parts of styrene-acrylic emulsion, 8 parts of acrylic emulsion, 15 parts of epoxy resin emulsion, 8 parts of polyvinyl alcohol, 30 parts of inorganic particles, 10 parts of auxiliary agent, 1.5 parts of plasticizer, 1 part of defoaming agent, and 2 parts of bactericide.
[0062] The preparation method of the styrene-acrylic emulsion is as follows: Calculated by weight, 30 parts of styrene and 25 parts of butyl acrylate are added into a reaction kettle. After heating to 75°C, 2 parts of anionic emulsifier, 5 parts of oxidant, and 5 parts of reductant are added. After reacting for 5 hours, the temperature is lowered to 35°C to obtain the product.
[0063] The anionic emulsifier is sodium dodecyl benzene sulfonate.
[0064] The oxidant is tert-butyl hydroperoxide.
[0065] The reductant is thiourea dioxide.
[0066] The solid content of the acrylic emulsion is 45-50%, and the viscosity is 3000-5000 mPa·s.
[0067] The acrylic emulsion is purchased from 1108S produced by BASF Corporation, USA, the supplier.
[0068] The epoxy equivalent of the epoxy resin emulsion is 210-230 g / mol.
[0069] The epoxy resin emulsion is purchased from WSR 6101 produced by Shandong Pinsheng New Materials Co., Ltd., the supplier.
[0070] The viscosity of the polyvinyl alcohol is 21-26 cps, the relative molecular mass is 118000-124000, and the average molecular polymerization degree is 1700-1800.
[0071] The polyvinyl alcohol is purchased from polyvinyl alcohol BP-17 produced by Changchun Chemical Co., Ltd., Taiwan, China.
[0072] The inorganic particles are calcium carbonate and kaolin.
[0073] The weight ratio of the calcium carbonate to the kaolin is 1:1.
[0074] The particle size of the calcium carbonate is 800 mesh.
[0075] The calcium carbonate is purchased from the ultrafine calcium carbonate powder CC902 produced by the supplier Guangxi Hezhou Kelong Powder Co., Ltd.
[0076] The particle size of the kaolin is 1250 mesh.
[0077] The kaolin with a particle size of 1250 mesh is purchased from the kaolin produced by the supplier Runshi Mineral Powder Factory.
[0078] The auxiliary agent is a film-forming auxiliary agent.
[0079] The film-forming auxiliary agent is 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate.
[0080] The auxiliary agent is purchased from the film-forming auxiliary agent produced by the supplier Guangzhou Hengyu Chemical Co., Ltd.
[0081] The defoaming agent contains silicone components; the density of the defoaming agent is 0.5 - 1.5 g / cm 3 , and the viscosity is 100 - 300 mPa·s.
[0082] The defoaming agent is purchased from the defoaming agent SI 2293 produced by the supplier BASF. SI 2293.
[0083] The plasticizer is a non-phthalate plasticizer.
[0084] The specific gravity of the plasticizer is 0.1 - 2 (20 °C), and the volatilization loss is less than 15%.
[0085] The plasticizer is purchased from Eastman 168 produced by the supplier Eastman Chemical Company, USA.
[0086] The main component of the bactericide is 7-ethylbicyclooxazolidine.
[0087] The active ingredient of the bactericide is 90 - 100%, and the surface tension is 30 - 40 dynes / cm.
[0088] The bactericide is purchased from the mildew-proof bactericide BIOBANTM CS-1246 produced by the supplier Dow Chemical Company, USA.
[0089] The second aspect of the present invention provides a preparation method of the high-temperature resistant two-component high-frequency wood splice adhesive as described above, comprising the following steps:
[0090] S1. Prepare styrene-acrylic emulsion;
[0091] S2. Preparation of polyvinyl alcohol solution: Add polyvinyl alcohol and water into a reaction kettle, heat to 90 °C, stir for 2 h, and then cool down to 35 °C to obtain it.
[0092] S2. Mix the prepared styrene-acrylic emulsion, acrylic emulsion, epoxy resin emulsion and polyvinyl alcohol, and add them into a reaction kettle and stir for 35 min;
[0093] S3. Add inorganic particles into the solution of step S2, and stir at a temperature of 25 °C for 4 h;
[0094] S4. Add additives, plasticizers, defoamers and bactericides into the solution of step S3, and add appropriate deionized water to adjust the viscosity to 10000 cps and the solid content to 55%;
[0095] S5. Add sodium hydroxide into the solution of step S4, and adjust the pH value to 7 to obtain it.
[0096] In step S2, the solid content of polyvinyl alcohol in the polyvinyl alcohol aqueous solution is 20%.
[0097] Example 2
[0098] Example 2 provides a high-temperature resistant two-component high-frequency wood splice adhesive. The specific implementation method is the same as that of Example 1, and the difference is that its preparation raw materials include: 20 parts of styrene-acrylic emulsion, 30 parts of acrylic emulsion, 15 parts of epoxy resin emulsion, 8 parts of polyvinyl alcohol, 30 parts of inorganic particles, 10 parts of additives, 1.5 parts of plasticizer, 1 part of defoamer, and 2 parts of bactericide.
[0099] Example 3
[0100] Example 3 provides a high-temperature resistant two-component high-frequency wood splice adhesive. The specific implementation method is the same as that of Example 1, and the difference is that the defoamer does not contain silicon; the defoamer is purchased from Degussa TEGO920 defoamer.
[0101] Example 4
[0102] Example 4 provides a high-temperature resistant two-component high-frequency wood splice adhesive. The specific implementation method is the same as that of Example 1, and the difference is that the inorganic particles are calcium carbonate.
[0103] Example 5
[0104] Example 5 provides a high-temperature resistant two-component high-frequency wood splice adhesive. The specific implementation method is the same as that of Example 1, and the difference is that its preparation raw materials include: 48 parts of styrene-acrylic emulsion, 8 parts of acrylic emulsion, 8 parts of polyvinyl alcohol, 30 parts of inorganic particles, 10 parts of additives, 1.5 parts of plasticizer, 1 part of defoamer, and 2 parts of bactericide.
[0105] The high-frequency splicing adhesive produced in Examples 1-5 is a two-component adhesive, which is mixed with polymeric MDI at a weight ratio of 100:15 to obtain a mixed adhesive. The mixed adhesive is bonded between two standard beech test blocks of 100mm×75mm×75mm. The area of the bonding surface is 75mm×75mm, and the single-sided glue application amount is 140 g / m² of the mixed adhesive. It is prepared by a high-frequency machine, cured at a frequency of 50Khz, and the curing time is 90 seconds - 180 seconds. Then its performance is tested. The polymeric MDI is purchased as M200 from Mitsui of Japan.
[0106] Performance test method
[0107] 1. Shear strength
[0108] For the specimens prepared in Examples 1-5, the shear strength after being placed at room temperature for three days is measured according to JIS K6806-2003 of Japan, and the results are recorded in Table 1.
[0109] 2. Immersion peel test
[0110] For the specimens prepared in Examples 1-5, the immersion peel strength is measured according to GB / T18103-2000 of China. After the specimens are bonded, they are placed at room temperature for 7 days, then soaked in water at 25°C for 6 hours, and then put into a constant temperature drying oven at 40°C and dried for 18h. Observe whether there is glue opening, peeling and delamination in the glue layer. If the glue opening rate of the splicing glue layer is less than 10% and the glue opening rate of a single glue line is less than one-third, it is qualified.
[0111] The number of specimens in Examples 1-5 is 10 respectively. The glue opening of the splicing glue layer is the separation between two wooden boards. The glue opening rate of the splicing glue layer is the number of separated samples / the total number of samples (40); the glue opening of a single glue line is the cumulative sum of the lengths of the peeled parts on each side of each glue layer greater than 0.3mm. The glue opening rate of a single glue line is the number of glue layers with the cumulative sum of the peeled parts greater than 0.3mm / the total number of glue layers (160). The results of Examples 1-5 are recorded in Table 1.
[0112] Table 1
[0113]
Claims
1. A high-temperature resistant two-component high-frequency wood splicing adhesive, characterized in that, By weight, it contains the following raw materials: 30-50 parts of styrene-acrylic emulsion, 5-10 parts of acrylic emulsion, 10-25 parts of epoxy resin emulsion, 5-10 parts of polyvinyl alcohol, 20-40 parts of inorganic particles, 10-20 parts of additives, 1-2 parts of plasticizer, 1-2 parts of defoamer, 1-2 parts of bactericide, and 1-10 parts of alkali; The solid content of the acrylic emulsion is 40-60%, and the viscosity is 2000-7000 mPa·s; The mass ratio of the acrylic emulsion to the styrene-acrylic emulsion is 1:(6-10); The inorganic particles are calcium carbonate and kaolin, and the weight ratio of the calcium carbonate to the kaolin is (1-2):(1-2); The particle size of the calcium carbonate is 400-1200 mesh; The particle size of the kaolin is 1000-2000 mesh.
2. The high-temperature resistant two-component high-frequency wood splicing adhesive according to claim 1, wherein, By weight, it contains the following raw materials: 35-50 parts of styrene-acrylic emulsion, 5-8 parts of acrylic emulsion, 15-20 parts of epoxy resin emulsion, 5-8 parts of polyvinyl alcohol, 20-35 parts of inorganic particles, 10-15 parts of additives, 1-2 parts of plasticizer, 1-2 parts of defoamer, 1-2 parts of bactericide, and 3-8 parts of alkali.
3. A high-temperature resistant two-component high-frequency wood splicing adhesive according to any one of claims 1-2, characterized in that, The viscosity of the polyvinyl alcohol is 5-30 cps, and the relative molecular mass is 20000-100000.
4. A high-temperature resistant two-component high-frequency wood splicing adhesive according to claim 1, characterized in that, The defoamer contains silicone components.
5. The high-temperature resistant two-component high-frequency wood splicing adhesive according to claim 4, wherein, The density of the defoamer is 0.5 - 1.5 g / cm 3 , and the viscosity is 100 - 300 mPa·s.
6. A preparation method of a high-temperature resistant two-component high-frequency wood splicing adhesive according to any one of claims 1-5, characterized in that, It includes the following steps: S1. Prepare the styrene-acrylic emulsion; S2. Prepare the polyvinyl alcohol solution: Add polyvinyl alcohol and water to the reaction kettle, heat to 80-100 °C, stir for 1-3 h, and then cool to below 40 °C to obtain it; S3. Mix the prepared styrene-acrylic emulsion, acrylic emulsion, epoxy resin emulsion, and polyvinyl alcohol solution, and add them to the reaction kettle and stir for 20-40 min; S4. Add inorganic particles to the solution in step S3, and stir at a temperature of 20-30 °C for 2-5 h; S5. Add additives, plasticizer, defoamer, and bactericide to the solution in step S4, and add an appropriate amount of deionized water to adjust the viscosity to 5000-20000 cps and the solid content to 50-60%; S6. Add alkali to the solution in step S5, and adjust the pH value to 5-7 to obtain it.
Citation Information
Patent Citations
Single-component laminating glue and preparation method thereof
CN103409087B
Wood splicing adhesive
CN108018006A
Boiling-water-resistant double-ingredient water-soluble plate splicing adhesive
CN107573884A